Explaining cross-country heterogeneity in trust in physicians: the role of pharmaceutical expenditure - Hsieh, Chee-Ruey (Unpublished, 2019)
Trust in physicians is the fundamental social mechanism in the health sector to address the issue of uncertainty in the effectiveness of health care and asymmetric information between patients and physicians. As health systems are so diverse in the world, there are substantial differences across nations in trust in physicians. Few studies have paid attention to the link between the characteristics of health system and patient trust in physicians. This study used 2011 International Social Survey Programme data to explore the potential mechanism in accounting for cross-country heterogeneity in trust in physicians. We hypothesize that physician-induced demand in the pharmaceutical sector shapes the perception that physicians serve as imperfect agents to their patients, which in turn lowers trust in physicians. Specifically, we used the share of pharmaceutical expenditure in total health expenditure as a proxy measure of physician-induced demand in prescription drugs, and we found that individuals were more likely to believe that physicians serve as imperfect agent if their countries spend a high share of health care costs on pharmaceutical products. In addition, our cross-country analysis shows a significant negative relationship between the perception of imperfect agency and trust in physicians.